A case study about cooperation between university research centres: Knowledge transfer perspective - Mário Franco; Cláudia Pinho (Journal of Innovation & Knowledge (JIK), 2019)
The aim of this study is to provide a wide-ranging view of the benefits and obstacles of cooperation between University Research Centres. To do so, the four dimensions associated with knowledge transfer, choice of partners, culture and financing were considered. A qualitative approach was adopted, and within this the case study method: the SiNGULAR project. Data were obtained from various in-depth interviews, documentary analysis and the official site of the project. Based on the results obtained, it is concluded that knowledge transfer, choice of partners and finance stimulate this type of cooperation, and that cultural differences between researchers and research centres are a bonus for this cooperation. Several implications for theory and practice are also presented.
Keywords: M10; M13; M21; 650; University Research Centres; Cooperation; Culture; Financing; Partnerships; SiNGULAR project; Knowledge transfer